2010
DOI: 10.1644/09-mamm-a-334.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of American pikas in a low-elevation lava landscape: conservation implications from the range periphery

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(137 citation statements)
references
References 63 publications
(143 reference statements)
5
128
1
Order By: Relevance
“…snow blanketing the talus acts to insulate pikas from extreme cold. Beever et al (2010) found below-talus temperatures to be colder in the absence of snow, and acute cold stress (defined as number of days with below-talus temperatures less than −5°C) to be among the better predictors of pika persistence in the Great Basin. hik (2007, 2010) reported the collapse of a population of Collared Pikas in the Yukon by 90% between 1998 and 2003, a period with later spring snowmelt associated with negative Pacific decadal oscillation values.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…snow blanketing the talus acts to insulate pikas from extreme cold. Beever et al (2010) found below-talus temperatures to be colder in the absence of snow, and acute cold stress (defined as number of days with below-talus temperatures less than −5°C) to be among the better predictors of pika persistence in the Great Basin. hik (2007, 2010) reported the collapse of a population of Collared Pikas in the Yukon by 90% between 1998 and 2003, a period with later spring snowmelt associated with negative Pacific decadal oscillation values.…”
Section: Discussionmentioning
confidence: 93%
“…Concerns over the effects of climate change on pikas arise from several sources including observations of population disappearance (Beever et al 2003(Beever et al , 2011stewart et al 2015), elevational retreat (Beever et al 2003(Beever et al , 2011Grayson 2005;Millar and Westfall 2010), susceptibility to acute (MacArthur and Wang 1974;smith 1974a) and chronic heat stress (Beever et al 2010;Wilkening et al 2011;stewart et al 2015), increasing frequency of low precipitation and snowpack (erb et al 2011;Beever et al 2013;Jeffress et al 2013), limited dispersal ability (seppänen et al 2012;Beever and smith 2013), restriction to areas of permafrost (hafner 1993, 1994Millar and Westfall 2010;Wilkening et al 2015), dependence on higher elevations (Rodhouse et al 2010), and habitat change (CoseWiC 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Populations near the edge of the range of the species often deal with limiting factors that differ in comparison to populations in the core of the range, including changes in predation pressure (Vaupel and Matthies 2012), food availability (Ferguson and McLoughlin 2000), temperature (Sanford et al 2006), growing season (Normand et al 2009), and of increasing concern, climate (Opdam and Wascher 2003;Böhning-Gaese and Lemoine 2004;Moritz et al 2008;Rodhouse et al 2010). Conservation biologists and wildlife managers require the best natural history and ecology data to make informed decisions, but variation in limiting factors and differential response to them are often poorly documented, complicating the decision making process (Dayton 2003;Greene 2005;Bury 2006).…”
Section: Introductionmentioning
confidence: 99%